Perkembangan kecerdasan buatan dalam menciptakan model pemasaran baru: artificial intelligence - tanzilia, lailatut (Maliki Interdisciplinary Journal, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed modern digital marketing practices. AI enables companies to process large amounts of data, identify consumer behavior patterns, and design more targeted marketing strategies. This study examines how AI reshapes marketing models, the new approaches that emerge, and the extent to which AI influences campaign effectiveness and company–consumer relationships. This research uses a literature review method by analyzing scientific publications from 2020–2024 related to AI and digital marketing. The findings indicate that AI integration generates personalized, predictive, automated, and conversational marketing models. These approaches enhance audience targeting accuracy, campaign efficiency, and consumer engagement. However, the use of AI also raises ethical concerns, especially regarding data privacy and algorithmic fairness. Overall, this study highlights the importance of implementing AI responsibly to maintain consumer trust and ensure sustainable digital marketing practices.